A decade-long clinical experience on the prophylactic use of activated prothrombin complex concentrate in acquired haemophilia A: a case series from a tertiary care centre. Issue 3 (April 2018) - Árokszállási, Anita; Rázsó, Katalin; Ilonczai, Péter; Oláh, Zsolt; Bereczky, Zsuzsanna; Boda, Zoltán; Schlammadinger, Ágota
Abstract : N/A: In acquired haemophilia A (AHA), risk for recurrent bleeding exists until the inhibitor is detectable. Thus, patients with persisting inhibitor may benefit from prophylaxis with activated prothrombin complex concentrate (aPCC). Potential thromboembolic complications and cost are also factors to consider. Today, no high level evidence or clear recommendations are available on aPCC prophylaxis in AHA. Recently, a small prospective study demonstrated a favourable outcome with short-term, daily administered aPCC infusion. Here we report a retrospective case series of 19 patients with AHA to demonstrate our practice on aPCC prophylaxis. In our practice, clinical bleeding tendency guided our decision on the initiation of aPCC prophylaxis. In patients with serious bleeding tendency, aPCC infusion was prolonged beyond bleeding resolution in a twice-weekly or thrice-weekly regimen. Serious bleeding phenotype included a single episode of life-threatening bleeding or recurrent, severe haemorrhages. Patients who did not present such events were treated on-demand. The preventive dose of aPCC was equal with the lowest effective therapeutic dose. Prophylaxis was continued until the inhibitor disappeared. Eleven patients received aPCC prophylaxis. In nine cases, prophylaxis lasted beyond two months. No severe bleeding developed spontaneously and no thromboembolic complication occurred in the median 16 weeks (interquartile range 9–34) duration of prophylaxis. Eight patients of the nonprophylaxis group did not present any severe haemorrhage. According to our experience, we consider prophylaxis with aPCC effective and well tolerated for patients with AHA and serious bleeding tendency, until the acquired inhibitor persists.